Rumah Tinggal dengan Struktur Bambu Plester - Adhi Risnandar, Firman Fadhly; Tambunan, Lily; Wonorahardjo, Surjamanto (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
Plastered bamboo is a traditional construction method that has been around for a long time. However, its application is not yet widely known by the public. In the problem of providing low-cost housing, plastered bamboo can be one of the solution to overcome this problem. The purpose of this study was to compare the construction costs of plastered bamboo houses with conventional houses. Data collection methods were through observation and literature review. The results of the study showed that plastered bamboo houses have the potential to be developed as an alternative to providing houses for low-income communities